(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Contemporary climate change has precipitated the desiccation of the Aral Sea (Lake) as well as Lakes Chad and Urmia. The first two lakes repeatedly sharply lost their water volume during severe droughts for quite a long time, and during wet periods they recovered again. Periods of severe droughts and humidification of their basins have been identified. Their current desiccation began in the 1960s and is developing according to a similar scenario. Lake Urmia lost its prehistoric water volume due to the tectonic subsidence of its basin at the end of the Late Pleistocene. In more recent times, fluctuations in its level have been mainly associated with changes in climatic conditions. The current desiccation of all three lakes coincided with a new dry climate cycle, which was superimposed by anthropogenic impact, that have culminated in catastrophic consequences. The lakes can be saved only by completely abandoning the use of river runoff for agricultural purposes. The lakes will gradually recover during the wet climate cycle, which may replace the current dry phase.